East Asian Men : Masculinity, Sexuality and Desire - Lin, Xiaodong; Haywood, Chris; Mac an Ghaill, Mairtin (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book provides a fresh and contemporary take on the study of men and masculinity. It highlights new and exciting approaches to sexuality, desire, men and masculinity in East Asian contexts, focusing on the interconnections between them. In doing so, it re-examines the key concepts that underpin studies of masculinity, such as homophobia, homosociality and heteronormativity. Developing new ways of thinking about masculinity in local contexts, it fills a significant lacuna in contemporary scholarship. This thought-provoking work will appeal to students and scholars of gender studies, cultural studies and the wider social sciences.- Resumé vydavatel
Keywords: sexuální chování -- Asie východní; maskulinita -- Asie východní; muži -- Asie východní; gender -- Asie východní; sexual behavior -- Asia, Eastern; masculinity -- Asia, Eastern; men -- Asia, Eastern; gender -- Asia, Eastern; elektronické knihy; kolektivní monografie; electronic books; collective monographs